2014
DOI: 10.1007/s00384-014-2063-z
|View full text |Cite
|
Sign up to set email alerts
|

Hilar cholangiocarcinoma: Controversies on the extent of surgical resection aiming at cure

Abstract: BackgroundHilar cholangiocarcinoma is the most common malignant tumor affecting the extrahepatic bile duct. Surgical treatment offers the only possibility of cure, and it requires removal of all tumoral tissues with adequate resection margins. The aims of this review are to summarize the findings and to discuss the controversies on the extent of surgical resection aiming at cure for hilar cholangiocarcinoma.MethodsThe English medical literatures on hilar cholangiocarcinoma were studied to review on the relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
57
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 98 publications
0
57
3
1
Order By: Relevance
“…Even though the intraoperative assessment of bile duct margin clearance is a useless prognostic marker for patients undergoing resection for HCCA in few reports, frozen section analysis of bile duct margins is the most used method to guide the extent of surgical resection for HCCA. The accuracy, sensitivity, and specificity of 89, 68, and 97%, respectively, of intraoperative FS in this study are higher than those of 56.5, 75.0, and 46.7% reported by Okazaki et al. except sensitivity.…”
contrasting
confidence: 77%
See 2 more Smart Citations
“…Even though the intraoperative assessment of bile duct margin clearance is a useless prognostic marker for patients undergoing resection for HCCA in few reports, frozen section analysis of bile duct margins is the most used method to guide the extent of surgical resection for HCCA. The accuracy, sensitivity, and specificity of 89, 68, and 97%, respectively, of intraoperative FS in this study are higher than those of 56.5, 75.0, and 46.7% reported by Okazaki et al. except sensitivity.…”
contrasting
confidence: 77%
“…Even though the intraoperative assessment of bile duct margin clearance is a useless prognostic marker for patients undergoing resection for HCCA in few reports, frozen section analysis of bile duct margins is the most used method to guide the extent of surgical resection for HCCA. [2] The accuracy, sensitivity, and specificity of 89, 68, and 97%, respectively, of intraoperative FS in this study are higher than those of 56.5, 75.0, and 46.7% reported by Okazaki et al [3] except sensitivity. It suggests us that these are unlikely to be totally objective, besides the specific pathologic features of the tumor, these are determined by different Abstract Mantel et al showed that the use of intraoperative frozen section analysis of the proximal bile ducts has a limited contribution in obtaining secondary R0 resections and final resection status had no impact on recurrence rate in hilar cholangiocarcinoma.…”
contrasting
confidence: 64%
See 1 more Smart Citation
“…Over the last two decades, several studies have demonstrated improved survival in patients with hilar cholangiocarcinoma treated with bile duct resection and major hepatic resection as a result of increased R0 resection rates . A recent analysis of hilar cholangiocarcinoma resected with combined major hepatic resection demonstrated a positive correlation with the tumour‐free resection margin rate . Reported rates of postoperative morbidity and mortality ranged from 6% to 52% and from 2% to 12%, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis found mortality after hepatectomy for PCC of 3.7%. 81,82 The 5-year survival, although longer, has not been significantly different in R0 and R1 resections. 83,84 Achievement of R0 and R1 surgical margins in non-metastatic disease has been associated with median survival of 40-74 months and 9-24 months respectively in some studies.…”
mentioning
confidence: 95%